2017
DOI: 10.1097/rlu.0000000000001460
|View full text |Cite
|
Sign up to set email alerts
|

Intense Uptake in Amyloidosis of the Seminal Vesicles on 68Ga-PSMA PET Mimicking Locally Advanced Prostate Cancer

Abstract: We report a case of benign senile seminal vesicle amyloidosis demonstrating intense Ga-prostate-specific membrane antigen (PSMA) uptake on PET/CT. A 68-year-old man underwent staging PSMA PET/CT and MRI for biopsy-proven prostate adenocarcinoma. There was an intense focus of Ga-PSMA uptake in the primary malignancy, as well as symmetrical intense uptake in the seminal vesicles bilaterally that was reported as multifocal disease with local invasion. Final histology after radical prostatectomy showed amyloidosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In the late 1990s it was found that the neovasculature of many solid tumours also expresses PSMA [13]. Recently, there have been many reports of the uptake of PSMA ligands in various nonprostate tissues [14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…In the late 1990s it was found that the neovasculature of many solid tumours also expresses PSMA [13]. Recently, there have been many reports of the uptake of PSMA ligands in various nonprostate tissues [14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…3 The avidity in some of these cases has been ascribed to the PSMA expression in the endothelial cells of the tumor neovasculature. 4 A few more case reports showing nonmalignant causes of PSMA uptake in nonneoplastic processes [5][6][7][8][9][10][11][12][13] and in benign neoplasms [14][15][16][17][18][19][20][21][22][23] are reported in the literature. Spindle cell lipoma is a rare variant of lipoma, characterized by mature adipocytes and small uniform spindle cells.…”
mentioning
confidence: 99%